Comparative study of the linear and nonlinear optical properties for different Iraqi heavy and light crude oils - Mahmood, Aseel I.; Fandi, Sawsan K.; Naser, Hayder A. (Iraqi Journal of Physics, 2020)
Iraqi oil crudes have some of the physical and chemical characteristics that distinguish it from other types of oil crudes in the world. Some of these features such us molecular composition, rheological, viscosity and emulsions are studied carefully by researchers. In this work, a comparative study of the linear and the non-linear optical properties for typical heavy and light crude oils of Iraqi origin was studied utilizing Z-scan technique. The He -Ne laser of wavelength 632.8 nm had been used for this purpose. These samples were collected from Basra and Kut oil fields. The values of the non-linear refractive index (n2), non-linear absorption coefficient (β), and third-order electrical susceptibility (χ3) were estimated respectively. The obtained results show that Iraqi oil has a significant linear and non-linear optical properties.